1988
DOI: 10.1093/jn/118.9.1075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Fiber on the Metabolizable Energy of Human Diets

Abstract: Two diets consisting of natural foods that differed in fiber content were fed to 12 men for 6 wk each in a crossover design. Diet 1 contained 37 g total dietary fiber (TDF) from fruits and vegetables and diet 2 contained 16 g TDF from fruit and vegetable juices in a 2800-kcal menu. Seven-day food, urine and fecal composites were made and analyzed for their gross energy, fat, protein and carbohydrate content during the fourth and fifth weeks of each dietary consumption period. The metabolizable energy (ME) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
23
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…This is thought to be mediated via a suppression of hunger and food intake, as well as a reduction in apparent nutrient digestibility (Astrup et al, 2010). In our study, we observed an B3% reduction in apparent energy digestibility with the addition of 102 g/10 MJ oat bran to a low-fiber diet, which has been observed before using similar doses of oat bran (Calloway and Kretsch, 1978;Chen et al, 1998), as well as other types of soluble dietary fibers, such as wholegrain rye (Wisker et al, 1996), a fiber mixture from grains, cereals and citrus (Rigaud et al, 1987), and a diet with mixed cereal fibers (Miles et al, 1988). It has been estimated that the gradual weight gain of 0.5-1 kg/year in American adults can be explained by a positive energy balance of o200 kJ/day in most people (Hill, 2006), implying a potential for increased consumption of oat products in body weight management as part of a 'small changes strategy' aimed at reducing positive energy balance.…”
Section: Discussionsupporting
confidence: 81%
“…This is thought to be mediated via a suppression of hunger and food intake, as well as a reduction in apparent nutrient digestibility (Astrup et al, 2010). In our study, we observed an B3% reduction in apparent energy digestibility with the addition of 102 g/10 MJ oat bran to a low-fiber diet, which has been observed before using similar doses of oat bran (Calloway and Kretsch, 1978;Chen et al, 1998), as well as other types of soluble dietary fibers, such as wholegrain rye (Wisker et al, 1996), a fiber mixture from grains, cereals and citrus (Rigaud et al, 1987), and a diet with mixed cereal fibers (Miles et al, 1988). It has been estimated that the gradual weight gain of 0.5-1 kg/year in American adults can be explained by a positive energy balance of o200 kJ/day in most people (Hill, 2006), implying a potential for increased consumption of oat products in body weight management as part of a 'small changes strategy' aimed at reducing positive energy balance.…”
Section: Discussionsupporting
confidence: 81%
“…Each of these attributes has been associated with weaker effects on appetite and dietary compensation. [52][53][54][55][56][57][58][59] The absolute and relative importance of these properties, and others, has not been established, but warrant exploration. In summary, the present trial supports an independent effect of food rheology on energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…66 Higher fiber levels in foods can also result in energy loss. 67,68 Thus, it is biologically plausible that energy-yielding beverages will exert weaker appetitive and compensatory dietary responses than solid foods and thereby lead to positive energy balance and weight gain. Professor Anderson poses five key questions in his analysis that provide a logical format for delving further into the issue of beverages and obesity.…”
mentioning
confidence: 99%